2006
DOI: 10.1002/mop.22074
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sweep method of moments analysis of electromagnetic scattering from 3D targets on ocean‐like rough surfaces

Abstract: This paper presents the multiple sweep method of moments (MSMM) analysis of electromagnetic (EM) scattering from three dimensional (3D) targets on ocean-like rough surfaces. The MSMM is a recursive method for solving the large matrix equations which arise in the method of moments (MoM) analysis of electrically large bodies. In the MSMM, the body is split into P sections and the currents on these sections are found in a sequential downrange-uprange fashion. The first sweep includes the dominant scattering mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In addition, scattering patterns for several surface impedance values are presented and according to this numerical results it can be concluded that as the impedance mismatch between the scatterer and the free space increases, maximum field intensity also increases. As a future work, this solution can be asymptotically evaluated in order to improve higher order propagation models for terrain profiles [19]- [22]. In addition, contribution of the scatterer to the edge currents can be calculated by evaluating the scattered field in the paraxial region to be used as a benchmark solution for equivalent edge current approaches [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, scattering patterns for several surface impedance values are presented and according to this numerical results it can be concluded that as the impedance mismatch between the scatterer and the free space increases, maximum field intensity also increases. As a future work, this solution can be asymptotically evaluated in order to improve higher order propagation models for terrain profiles [19]- [22]. In addition, contribution of the scatterer to the edge currents can be calculated by evaluating the scattered field in the paraxial region to be used as a benchmark solution for equivalent edge current approaches [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…The document shows the results of the query mesh, while coarse mesh grid cells 440 become symbiotic, the study was divided into a grid space of 11 × 20 × 2, the x-axis direction 11, so according microstrip antenna along the x-axis length L is 28mm, so the average grid cell size of 2.54mm, the length minus 1.27mm, continue to be the coarse mesh grid, and the results of HFSS simulation analysis, the analysis is complete after determining the computation time of 3 minutes 52 seconds, sweep analysis results, as well as absorbing boundary microstrip antenna electric field distribution inside the magnetic field distribution, as shown in Fig.6-7: Fig. 7 absorbing boundary and the electric field distribution of the magnetic field distribution inside the microstrip antenna As can be seen from the simulation results, the use of improved algorithm sweep analysis results [ 10 ] , as well as absorbing boundary of the magnetic field distribution of the electric field distribution inside the microstrip antenna is basically the same, so verify the rationality of this algorithm.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Let and be the current and excitation vectors for the th block, respectively, and the matrix block containing the interactions between groups and is . The exact solution for given that is known, for , can be found by solving (4) where is the th diagonal (self) block. Next step is to construct a set of high-level basis functions, namely the CBFs, which represent each block (a portion of the terrain profile) by using (4)…”
Section: Formulationmentioning
confidence: 99%